Liquid-Supported Dentures: A Soft Option—A Case Report. (11th March 2013) - Jain, Anoop; Puranik, Shivakumar; Jagadeesh, M. S.; Kattimani, Puttaraj; Akki, Savita; Kumar, Pawan; laxmi', Vijaya
Abstract : Liquid-supported denture technique allows continued adaptation of denture to the mucosa both at resting and functional state. A complete denture prosthesis is unacceptable if it violates the foundation on which it rests. In this case, a technique for fabrication of a complete denture prosthesis that eliminates the disadvantages of tissue conditioners and soft liners (i.e., poor bond strength to acrylic, candidal colonization, etc.) and preserves the remaining tissues is described. Liquid-supported denture can be a permanent solution to some patients with problematic conditions like diabetes, xerostomia, atrophied ridge, and so forth.